Distraction osteogenesis of the sternum for thoracic expansion in a severe case of jeune syndrome: a preliminary report. Issue 3 (3rd May 2016) - Imai, Yoshimichi; Kitanishi, Ryuta; Saiki, Yoshikatsu; Takeda, Atsushi; Tachi, Masahiro
Abstract: Severe asphyxiating thoracic dystrophy (Jeune syndrome) is usually fatal. The authors used distraction osteogenesis in a severe case and achieved 45 mm distraction of the sternum and improvement in tidal volume, lung compliance, and mean airway pressure.